TİP 2 DİYABETLİ HASTALARDA C VİTAMİNİ UYGULAMASININ ERİTROSİT GLUTATYON VE HBA1C DÜZEYLERİ ÜZERİNE ETKİSİ - Cengiz, Müjgan; CENGİZ, Salih (Cerrahpaşa Medical Journal, 2019)
Background and Design.- Diabetes mellitus (OM) has some complications. Oxidative stress plays an important role in the creation of these complications. At the other hand Vitamin C plays nonenzymatic antioxidant role in the organisms. The goal of our study was to compare glycosylated haemoglobine (HbAlc) and glutathione (GSH) levels of the 20 type 2 DM patients taking vitamin C with the 20 type 2 DM patients taking placebo. The amount of HbAlc by chromatographic elution and glutathione were measured by using capillary electrophoresis technique at the first day, first month and second month. Results.- After usage of vitamine C for one month, the values of HbAlc were decreased significantly but GSH levels were still without a significant difference. After usage of vitamine C for two months, the values of HbAlc were decreased significantly and GSH levels were increased significantly. After one and two months usage of placebo, the values of both HbAlc and GSH were still without a significant difference. Conclusion.- Comparison of the Vitamin C taking group with the plasebo receiving group showed that these findings and results must be considered as positive effect of the Vitamin C to the patients. This is because of the decreasing of the glycosylated haemoglobine and increasing of the glutathione levels. The glutathione levels are all found as in lower value when compared with non chromatographic method. This is because of the exact molecular prediction and measurement of the species.